Pendampingan Laporan Pajak Sesuai Peraturan Pemerintah No. 55 Tahun 2022 Wajib Pajak Di KPP Gayamsari Semarang - Nanang Ari Utomo; Abdul Manan; Andhy Tri Ardiyanto (CV. Multi Kreasi Media, 2023)
Based on the analysis of the situation, the problem faced by the community is a lack of knowledge about Government Regulation No. 55 of 2022 concerning final tax for UMKM with a sales turnover below Rp. 4,800,000,00.00. Therefore the Community Service team intends to provide outreach and assistance to Government Regulation no. 55 of 2022 for UMKM taxpayers to increase tax compliance. The implementation method used in this community service activity is the mentoring method through home visits, interviews and discussions. the Community Service team has the type of expertise that suits the needs of partners, namely taxation and accounting. Thus, with expertise that is in accordance with the needs of partners, it makes it easy for business owners as taxpayers who are registered at the Gayamsari Semarang KPP. The impact is that taxpayers can carry out tax obligations through an understanding of knowledge about the benefits of taxation for the community and the creation of taxpayer compliance in making payments and reporting periodic and annual tax returns.